An Evaluation on the Problems of Applied Courses Taught in Radio, Television and Cinema Departments - Altay, Recep; Kavuran, Tamer (Mutlu TÜRKMEN, 2021)
This study examined course curricula of Radio, Television and Cinema (RTC) departments Communication Faculties and aims to assess applicability levels of vocational courses with the physical and technical infrastructure also means within the framework of the views of the academicians. The study was conducted using the tarama model to academicians working at the Radio, Television and Cinema departments of Communication faculties. 140 academicians participated to the study and 70% usable data was obtained. As a result of the examination, it was seen that applied courses are very few or do not exist in the course curricula of some universities. Furthermore, it was found out that great majority of the courses are taught compulsorily. It was seen that the academicians attributed the low number of applied courses in the relevant department to insufficient physical and technical infrastructures of Communication faculties. At the end of the study, it was concluded that contents and applicability levels of vocational courses as ‘Camera and Light, News Collection, Writing and Photography’ are very insufficient, but sufficient in terms of course hours only. Chi square (X2) results were used to identify the impact of academic career and service durations on the applicability levels of branch courses of academicians.

Bu çalışmada, İletişim Fakültelerinin fiziki ve teknik alt yapı olanakları ile Radyo Televizyon ve Sinema (RTS) bölümlerinin ders müfredatları incelenmiştir. Ayrıca ilgili bölümdeki mesleki derslerin uygulanabilme düzeyleri, öğretim elemanlarının görüşleri çerçevesinde değerlendirilmesi amaçlanmıştır. Tarama modeli ile yapılan çalışma, İletişim Fakültelerinin Radyo Televizyon ve Sinema bölümlerinde görev yapan öğretim elamanları üzerinde gerçekleştirilmiştir. 140 öğretim elemanının katılım sağladığı araştırmada, % 70 kullanılabilir veri elde edilmiştir. İnceleme sonucunda bazı üniversitelerin ders müfredatlarında uygulamalı derslerin çok az olduğu ya da hiç yer almadığı görülmüştür. Ayrıca derslerin büyük çoğunluğunun zorunlu ders olarak okutulduğu tespit edilmiştir. Öğretim elemanlarının, ilgili bölümde uygulamalı derslerin az olmasını İletişim Fakültelerinin fiziki ve teknik alt yapılarının yeterli olmamasına bağladığı görülmüştür. Çalışmanın sonucunda, ‘Kamera ve Işık, Haber Toplama Yazma ve Fotoğrafçılık’ gibi mesleki derslerin içeriği ile uygulanabilme seviyelerinin çok yetersiz olduğu sonucuna ulaşılmıştır. Öğretim elemanlarının branş derslerin uygulanabilme düzeylerinde, akademik kariyer ve hizmet sürelerinin etkisini tespit etmek için kay kare (X2) sonuçlarına başvurulmuştur.
Radyo Televizyon ve Sinema Bölümlerinde Okutulan Uygulamalı Derslerin Sorunları Üzerine Bir Değerlendirme
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları